2019
DOI: 10.1111/irv.12707
|View full text |Cite
|
Sign up to set email alerts
|

Human matriptase/ST 14 proteolytically cleaves H7N9 hemagglutinin and facilitates the activation of influenza A/Shanghai/2/2013 virus in cell culture

Abstract: Background: Influenza is a zoonotic disease that infects millions of people each year resulting in hundreds of thousands of deaths, and in turn devastating pandemics.Influenza is caused by influenza viruses, including influenza A virus (IAV). There are many subtypes of IAV but only a few seem to be able to adapt to humans and to cause disease. In 2013, an H7N9 IAV subtype emerged in China that does not cause clinical symptoms in its chicken host but leads to severe infections when transmitted into humans. Sinc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 20 publications
(37 reference statements)
0
8
0
Order By: Relevance
“…The reports demonstrating that TMPRSS2 is crucial for H1N1 and H7N9 virus propagation in mice and cell culture suggest that it also plays a major role in the human respiratory tract. So far, however, it is unclear whether the obtained results translate to humans and other studies have shown that for example human matriptase is able to process H1N1 and H7N9 (Hamilton and Whittaker, 2013;Whittaker and Straus, 2019). Our peptide assay suggests that SPINT2 has a wide variety of host protease specificity.…”
Section: Discussionmentioning
confidence: 62%
“…The reports demonstrating that TMPRSS2 is crucial for H1N1 and H7N9 virus propagation in mice and cell culture suggest that it also plays a major role in the human respiratory tract. So far, however, it is unclear whether the obtained results translate to humans and other studies have shown that for example human matriptase is able to process H1N1 and H7N9 (Hamilton and Whittaker, 2013;Whittaker and Straus, 2019). Our peptide assay suggests that SPINT2 has a wide variety of host protease specificity.…”
Section: Discussionmentioning
confidence: 62%
“…In addition to being novel drugs, selective TMRSS2 inhibitors can be used as valuable chemical probes to help elucidate mechanisms of viral pathogenesis, including host cellÀvirus interactions, Spike protein processing, and ACE2 receptor binding. Since TMPRSS2 plays a key role as a viral protein processing protease in the pathogenesis of other coronaviruses (SARS-CoV, MERS-CoV) as well as influenza viruses (25,(54)(55)(56)(57)(58), MM3122 and this new class of inhibitors may be effective not only against COVID-19 but for infections caused by most or all corona and influenza viruses. Thus, these small-molecule inhibitors of TMPRSS2 not only hold much promise as new drugs to treat SARS-CoV-2 infections but also potentially represent broad-spectrum antivirals.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to being novel drugs, selective TMRSS2 inhibitors can be used as valuable chemical probes to help elucidate mechanisms of viral pathogenesis, including host cell-virus interactions, Spike protein processing and ACE2 receptor binding. Since TMPRSS2 plays a key role as a viral protein processing protease in the pathogenesis of other coronaviruses (SARS-CoV, MERS-CoV) as well as influenza viruses [47][48][49][50][51][52] , MM3122 and this new class of inhibitors may be effective not only against COVID-19 but for infections caused by most or all corona and influenza viruses. Thus, these small-molecule inhibitors of TMPRSS2 not only hold much promise as new drugs to treat SARS-CoV-2 infections but also potentially represent broad-spectrum antivirals.…”
Section: Discussionmentioning
confidence: 99%